Impact of Climate Change and Technology on Food Availability in Sumatera, Indonesia - Rizal Rahman H. Teapon; Harianto; Hermanto Siregar; Widyastutik (GoAcademica Research & Publishing, 2022)
This study explores the impact of climate change and technology on food supply and demand, which complements the limits of previous findings. The main foundations are Hessian food production and Marshallian demand theories. It aims to analyze the factors influencing food availability and the response of each variable, as well as simulate the effect of climate change and technology. Secondary data from the Food Security and the Central Statistics Agency of 10 provinces in Sumatra will be used between the periods of 2010 to 2019. Furthermore, this study uses the simultaneous method of 8 structural and 2 identity equations. The influencing variables of production include price, expected food pattern of grains and tubers, CPO price, temperature, rainfall, and irrigation network area. Meanwhile, consumption is influenced by price, poverty, food inflation, population, per capita income, and farmers’ exchange rate. The increase in temperature and rainfall reduces the production and consumption of rice, corn, cassava, and sweet potatoes. Meanwhile, technology development will increase food production and consumption. The availability is an essential dimension of food security that should be prioritized. Likewise, climate change and technology development need to be anticipated to mitigate these impacts.